Electrospun Iridium-Based Nanofiber Catalysts for Oxygen Evolution Reaction: Influence of Calcination on Activity-Stability Relation - Kovács, Miklós; Fritsch, Birk; Lahn, Leopold; Bachmann, Julien; Kasian, Olga; Mayrhofer, Karl; Hutzler, Andreas; Dworschak, Dominik (ACS Applied Materials and Interfaces, 2024)
The enhanced utilization of noble metal catalysts through highly porous nanostructures is crucial to advancing the commercialization prospects of proton exchange membrane water electrolysis (PEMWE). In this study, hierarchically structured IrOx-based nanofiber catalyst materials for acidic water electrolysis are synthesized by electrospinning, a process known for its scalability and ease of operation. A calcination study at various temperatures from 400 to 800 °C is employed to find the best candidates for both electrocatalytic activity and stability. Morphology, structure, phase, and chemical composition are investigated using a scale-bridging approach by SEM, TEM, XRD, and XPS to shed light on the structure-function relationship of the thermally prepared nanofibers. Activity and stability are monitored by a scanning flow cell (SFC) coupled with an inductively coupled plasma mass spectrometer (ICP-MS). We evaluate the dissolution of all metals potentially incorporated into the final catalyst material throughout the synthesis pathway. Despite the opposite trend of performance and stability, the present study demonstrates that an optimum between these two aspects can be achieved at 600 °C, exhibiting values that are 1.4 and 2.4 times higher than those of the commercial reference material, respectively. The dissolution of metal contaminations such as Ni, Fe, and Cr remains minimal, exhibiting no correlation with the steps of the electrochemical protocol applied, thus exerting a negligible influence on the stability of the nanofibrous catalyst materials. This work demonstrates the scalability of electrospinning to produce nanofibers with enhanced catalyst utilization and their testing by SFC-ICP-MS. Moreover, it illustrates the influence of calcination temperature on the structure and chemical composition of the nanofibers, resulting in outstanding electrocatalytic performance and stability compared to commercial catalyst materials for PEMWE.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Acidic water electrolysis; Catalyst morphology; Electrospinning; Enhanced catalyst utilization; Iridium oxide; Temperature-controlled synthesis